Improving Religious Literacy Through E-Learning In The Era Of Technological Disruptions - Deden Edi; Hardjadinata; Fajar Harguna Endra Putra; Dede Rosyada; Popi Puadah (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
The era of technological disruption brings challenges as well as great opportunities for the world of education, including in religious learning in Islamic universities. Universitas Islam Indonesia as an educational institution based on Islamic values ​​is faced with the demand to utilize information technology, especially e-learning, in religious learning. This study aims to examine the use of e-learning in improving students' religious literacy, with a focus on changing the learning paradigm from conventional to digital. Religious literacy in this context includes understanding, experiencing, and practicing Islamic teachings contextually and applicatively in modern life. The study used a descriptive qualitative approach, with data collection techniques through observation and interviews in online learning practices at Universitas Islam Indonesia. The results of the study show that the use of structured and innovative e-learning can be an effective medium in delivering Islamic material in an interesting, interactive, and relevant way for students. E-learning not only functions as a technical alternative, but also as a strategic solution in forming a generation of Muslims who are digitally competent and strong in religion. In conclusion, the application of e-learning in religious education in Islamic universities can be the key to facing the challenges of the era of disruption while strengthening students' religious literacy. Further research is recommended to explore the long-term impact of implementing e-learning on the development of students' religious character.